Violencia contra inmigrantes en Tamaulipas - Izcara-Palacios, Simón Pedro (European Review of Latin American and Caribbean Studies, 2012)
Abstract: Violence against immigrants in TamaulipasMigrants in Mexico are subjected to extortions, kidnappings, rapes and killings. Tamaulipas, a state situated in the northeast of Mexico, has registered an unprecedented level of violence against migrants. In August of 2010, 72 migrants were massacred in San Fernando (Tamaulipas) and in April of 2011, 194 corpses of migrants were found in the same place. Furthermore, since 2009, rural communities in central Tamaulipas, which receive more than five thousand migrants a year to work in harvesting oranges, have suffered violent attacks targeting immigrants. This paper, based on a qualitative methodology that includes in-depth interviews with 60 immigrants conducted between April 2011 and November 2011, examines the forms of cultural, direct, structural and post-structural violence suffered by immigrant workers employed in the orange sector of Tamaulipas.Resumen:Los migrantes en México son objeto de extorsiones, secuestros, violaciones y asesinatos. Tamaulipas, un estado situado en el noreste de México, ha registrado niveles sin precedentes de violencia contra los migrantes. En Agosto de 2010 72 migrantes fueron masacrados en San Fernando (Tamaulipas), y en Abril de 2011 194 cadáveres de migrantes fueron encontrados en el mismo lugar. Asimismo, las comunidades rurales del centro de Tamaulipas, que reciben anualmente más de 5 mil migrantes para trabajar en la pizca de la naranja, han sufrido desde el año 2009 violentos ataques dirigidos contra los migrantes. Este artículo, basado en una metodología cualitativa que incluye entrevistas en profundidad con 60 migrantes realizadas entre Abril y Noviembre de 2011, examina las formas de violencia cultural, directa, estructural y postestructural sufrida por los trabajadores migratorios empleados en el sector citrícola de Tamaulipas.